Determinan Minat Beli Smartphone Iphone: Perspektif Kualitas Produk, Gaya Hidup, Citra Merek, Word of Mouth, Desain Produk dan Persepsi Harga - Ade Sutrisna; Komsi Koranti; Aji Sukarno; Haryono; Budi Santoso (Forum Kerjasama Pendidikan Tinggi, 2024)
A smartphone is a mobile phone equipped with advanced features and high capabilities similar to a computer. The iPhone is a product of Apple that can function as one of the flagship smartphones. The purpose of this study is to examine and analyze the influence of product quality, lifestyle, brand image, word of mouth, product design, and price perception on the purchase intention of the iPhone smartphone. This research uses primary data with testing stages that include validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression, F test, t test, and coefficient of determination. Data collection was carried out using a questionnaire, with 152 respondents. The sampling method used in this study is non-probability sampling with purposive sampling technique, assisted by IBM SPSS Statistics 25 software. The results of the t-test show that the t-value is smaller than the t-table value for the following variables: Product Quality (0.318 < 1.658), Lifestyle (-0.790 < 1.658), Brand Image (0.389 < 1.658), Word of Mouth (0.988 < 1.658), and Product Design (0.808 < 1.658). These variables do not have a partial effect on the purchase intention of the iPhone smartphone in the Greater Jakarta area (Jabodetabek). However, Price Perception has a t-value greater than the t-table value (5.726 > 1.658), indicating that Price Perception has a partial effect on the purchase intention of the iPhone smartphone in the Greater Jakarta area. The results of the F test show that Product Quality, Lifestyle, Brand Image, Word of Mouth, Product Design, and Price Perception all have a simultaneous effect on the purchase intention of the iPhone smartphone in the Greater Jakarta area.